Synthesis of Urease Inhibitory 2, 4-bis (4-cyanobenzyl)glycoluril using Sandmeyer Reaction and Density Functional Theory Investigation - Yawer, Mirza Arfan; Bano, Shehar; Saleem, Muhammad; Yawer, Affiefa; Hussain, Riaz; Imran, Muhammad; Irfan, Ahmad; Rauf, Abdur; Abu-Izneid, Tareq (Current organic synthesis, 2021)
AIMS: The aim of the present research was to synthesize glycoluril derivative 2,4-Bis(4- cyanobenzyl)glycoluril through a convergent scheme. BACKGROUND: For this purpose, Sandmeyer reaction procedure was employed for the synthesis of said compound. The structure of the pure compound was confirmed by using different spectroscopic techniques, such as 1HNMR, 13C-NMR and (HR-MS) Mass spectrometry. OBJECTIVE: Convergent synthesis of 2,4-BIS (4-CYANOBENZYL)GLYCOLURIL USING SANDMEYER REACTION and urease inhibition study. METHODS: The structure of the pure compound was confirmed by using different spectroscopic techniques such as 1H-NMR, 13C-NMR and (HR-MS) Mass spectrometry. The electronic properties of the newly synthesized compound and thiourea were determined by using density functional theory. RESULTS: Furthermore, the compound was evaluated against urease enzyme and was found to be potent inhibitors with an IC50 value of 11.5 ± 1.50 μM when compared with standard inhibitor thiourea (IC50 = 21.0 ± 1.90 μM). The compound may serve as a lead compound to synthesize new cyano-based bambusuril in the future with enhanced biological properties. CONCLUSION: We have synthesized a new glycoluril derivative 2,4-Bis(4-cyanobenzyl)glycoluril by the sandmeyer reaction. It has been obtained in the form of light yellowish powder in good yield (96%). Glycoluril based macrocycles have been used in various fields; starting from the 2,4-Bis(4-nitrobenzyl)glycoluril (already reported compound), which has undergone reduction (CH3OH,Pt/C) , diazotization (NaNO2/HCl), cyanation (CuCl/KCN), respectively in order to synthesize the desired new glycoluril derivative. The obtained product will be used as a building block for the synthesis of the cyano based bambusuril marcocycle in the future. The yield of the obtained product has been monitored by using different amounts of cyanating reagent, but the best results are shown by the use of 4 mmol of CuCl/KCN. KCN with CuCl assisted the conversion of diazo group into the cyano group with enhanced yield when used in excess amount. It acts as a catalyst. The solubility characteristic of 2,4-Bis(4-cyanobenzyl)glycoluril has also been determined in different organic solvents. 1H NMR technique proved to be very helpful for the structure determination of our desired product. Benzylic protons give signals at 7.5 ppm and 7.8 ppm, respectively. The downfield peaks confirm the presence of CN group near the benzylic protons. Methine protons show a signal at 5.2 ppm, which ensures the basic skeleton of glycoluril. Ureidyl protons also confirm the synthesis of the heterocyclic 2,4-Bis(4-cyanobenzyl)glycoluril compound. The negative and positive electrostatic potential sites, molecular descriptors, and charge density distribution of frontier molecular orbitals are revealing that 4a with promising sites for electrophilic and nucleophilic attacks would result to enhance the urease inhibition, which is in good agreement with the experimental data.
Keywords: Enzyme Inhibitors; Imidazoles; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; Urease; ureasa; inhibitory enzymů; teorie funkcionálu hustoty; Density Functional Theory; imidazoly; Molecular Docking Simulation; simulace molekulového dockingu